KOMPRES JAHE BERKHASIAT DALAM MENURUNKAN INTENSITAS NYERI PADA PENDERITA RHEUMATHOID ARTHRITIS - Syapitri, Henny (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Rheumathoid disease and joint inflamation is the most diseases find in society, particularly in 40 years old. More than 40% from them suffer muscle pain. The objectives is knowing effect of ginger compresses in pain intensity who suffered Rheumathoid Arthtritis in 40 years old in Tiga Balata Health Center 2015. this study adopted quasy eksperimental method with pre-test and post test design. This research was conducted at Tiga Balata Health Center in march 06, 2015 until 20 march 2015. There are 30 respondens for this reseached who suffered rheumathoid arthritis and suffered pain. The sample in this research are with purposive sampling technique. Data collecting by interview and observation using interview and observation pain form. In this reseach noted that mostly respondent in their pain scale before ginger compresses (pre-test) at least 4,73 with standar deviasi 1.311. whereas pain intencity of rheumathoid arthritis after gingger comppresses (post-test) is 2,13 with deviasi standard 1,008. With wilcoxon sign rank test obtained such as rate of (p value = 000 < 0,05). This indicated that there is a significantly differences of pain intensity before ginger compresses with after ginger compresses (post-test). It is suggest to nurse that ginger compresses can use for complementary managing pain of rheumathoid arthritis could continue as intervention independent by patient. Advice for nursing practice that ginger compresses can use as complementary therapy to decrease pain intensity of rheumathoid arthritis.Keywords : Pain, Rheumathoid Arthritis, Ginger Compresses.